Preliminary study on modified foamed concrete-filled hollow section under cyclic load - Khairuddin, Siti Amirah Azra; Abd Rahman, Norashidah; Rossam, Mohd Luqman; Mustafa, Anis Nazirah (IOP Publishing, 2020)
The use of green materials has become a hot topic for discussion in steel construction. Foamed concrete is a green and lightweight material used in concrete mix. The use of foamed concrete as a fill in steel construction has been discussed by many researchers. However, the performance of foamed concrete under cyclic load has not been evaluated. Therefore, this study employed a modified foamed concrete-filled hollow section under cyclic load to determine the performance of concrete-filled hollow section under cyclic load. The modified foamed concrete consists of foamed concrete added with rice hush ash and fibre. Different types of fibres (steel and polypropylene fibres) were utilised. Results showed that the concrete-filled hollow section with steel fibre slightly improved the strength and ductility of the hollow section.